The role of networks in international acquisition premiums - Chengguang Li; Yadong Luo; Juan Bu; Yinuo Tang (Journal of International Business Studies, 2023)
Our work builds on network theory to investigate the role of alliance networks in international acquisition premiums. On the one hand, we postulate that an international acquirer's network centrality in the target country lowers the inclination of offering higher bid premiums associated with its liability of foreignness (i.e., negatively moderates the relation between foreignness and premiums). On the other hand, we provide a perspective that a target firm's local network centrality increases an international acquirer's willingness to pay higher premiums in order to gain access to unique and valuable local knowledge and resources (i.e., positively moderates the relationship between foreignness and premiums). To test our hypotheses, we analyzed a sample of 1693 related acquisition bids made in more than 40 countries between 2008 and 2017. Our findings support our dual perspective on the role of networks and demonstrate that the acquirer's networks and the target's networks have distinct influences on the relationship between foreignness and bid premiums. This study makes contributions to the understanding of the complex dynamics at play in international M&As and emphasizes the importance of distinguishing between the acquirer's and the target's networks in shaping acquisition premiums.
Keywords: 330; acquisition premium; network theory; alliance networks; international M&As; centrality